Red and far red Sun‐induced chlorophyll fluorescence as a measure of plant photosynthesis. Issue 6 (18th March 2015) - Rossini, M.; Nedbal, L.; Guanter, L.; Ač, A.; Alonso, L.; Burkart, A.; Cogliati, S.; Colombo, R.; Damm, A.; Drusch, M.; Hanus, J.; Janoutova, R.; et al.
Abstract: Remote estimation of Sun‐induced chlorophyll fluorescence emitted by terrestrial vegetation can provide an unparalleled opportunity to track spatiotemporal variations of photosynthetic efficiency. Here we provide the first direct experimental evidence that the two peaks of the chlorophyll fluorescence spectrum can be accurately mapped from high‐resolution radiance spectra and that the signal is linked to variations in actual photosynthetic efficiency. Red and far red fluorescence measured using a novel airborne imaging spectrometer over a grass carpet treated with an herbicide known to inhibit photosynthesis was significantly higher than the corresponding signal from an equivalent untreated grass carpet. The reflectance signal of the two grass carpets was indistinguishable, confirming that the fast dynamic changes in fluorescence emission were related to variations in the functional status of actual photosynthesis induced by herbicide application. Our results from a controlled experiment at the local scale illustrate the potential for the global mapping of terrestrial photosynthesis through space‐borne measurements of chlorophyll fluorescence. Key Points: A novel high‐resolution airborne sensor is flown Both red and far red Sun‐induced fluorescence signals are accurately quantified Red and far red fluorescence tracks variations in photosynthetic efficiency